Emerging preclinical evidence does not support broad use of hydroxychloroquine in COVID-19 patients - S. G. P. Funnell (Nature Portfolio, 2020)
There is an urgent need for drugs, therapies and vaccines to be available to protect the human population against COVID-19. One of the first approaches taken in the COVID-19 global response was to consider repurposing licensed drugs. This commentary highlights an extraordinary international collaborative effort of independent researchers who have recently all come to the same conclusion—that chloroquine or hydroxchloroquine are unlikely to provide clinical benefit against COVID-19.